Critical roles of key domains in complete adsorption of a beta peptide on single-walled carbon nanotubes: insights with point mutations and MD simulations - Jana, Asis K.; Jose, Jaya C.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2013)
Owing to the influence of nanomaterials on biomacromolecular behavior, their potential applications are rapidly gaining attention. Based on atomistic molecular dynamics simulation studies we have recently reported that the full-length A beta peptide, whose self-assembly is associated with Alzheimer's disease, adsorbs rapidly on single-walled carbon nanotubes, thereby losing its natural propensity to collapse. Here, we investigate the mechanistic overlap between the peptide's compactification and its adsorption, while decoupling the roles of hydrophobicity and aromaticity via point mutations. The collapse mechanism is correlated with interactions between the central hydrophobic core (HP1) and the peptide's C-terminal domain, which are almost exactly compensated by interactions arising from the nanotube after complete adsorption. Adsorption is initiated by HP1 and consolidated by strong interactions arising from the N-terminal domain. Altering the hydrophobicity, but not the aromatic character, of the central residue in HP1 decreases the collapse probability. On the other hand, the adsorption propensity is dramatically reduced when either the hydrophobicity or the aromatic character in HP1 is compromised. The hydrophobicity of HP1 is responsible for dewetting transitions that facilitate its initial interactions with the nanotube, which then lead to very favorable interactions with the nanotube.